3D printing of open-porous cellular ceramics with high specific strength. Issue 15 (December 2017) - Maurath, Johannes; Willenbacher, Norbert
Abstract: We present a novel processing route for manufacturing highly open porous, hierarchically structured ceramics via direct ink writing. We manufactured cellular samples with overall porosities up to 88% that exhibit fully open-porous struts with porosities between 45 and 60% and pore sizes x50, 3  < 6 μm using capillary suspension based inks. An innovative processing strategy enabled manufacturing crack-free, undeformed cellular ceramic samples. We printed hexagonal honeycomb structures that showed exceptionally high specific strength under compression load and significantly enlarged the strength-density range that was covered by sintered capillary suspensions, so far. Without loss of mechanical strength the density of ceramic parts was decreased by about a factor of 2–3. Strength of in-plane and out-of-plane loaded hexagonal honeycomb structures varies according to common scaling laws for cellular structures. The honeycombs are mechanically more efficient than bulk specimens from capillary suspensions, since they show a distinctly lower sensitivity of strength on density.